2015
DOI: 10.1111/tid.12395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of human immunodeficiency virus patients being referred for liver transplant evaluation: a descriptive cohort study

Abstract: Background Liver transplantation (LT) is a treatment option for select human immunodeficiency virus (HIV)-infected patients with advanced liver disease. The aim of this study was to describe LT evaluation outcomes in HIV-infected patients. Methods All HIV-infected patients referred for their first LT evaluation at the Mount Sinai Medical Center were included in this retrospective, descriptive cohort study. Multivariable logistic regression was used to identify factors independently associated with listing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Considering the high response rate of the specialized centers, the relatively small number of patients that were detected in our study probably comes close to the actual size of this very rare subgroup of patients in Germany. Our data correspond to different cohort studies stating a prevalence of 2.6–3.0% [ 41 , 42 ] for HCV/HIV-coinfected patients on the liver transplant waiting list, and a prevalence of 0.2–0.3% [ 43 , 44 ] for HCV/HIV-coinfected patients after liver transplantation.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the high response rate of the specialized centers, the relatively small number of patients that were detected in our study probably comes close to the actual size of this very rare subgroup of patients in Germany. Our data correspond to different cohort studies stating a prevalence of 2.6–3.0% [ 41 , 42 ] for HCV/HIV-coinfected patients on the liver transplant waiting list, and a prevalence of 0.2–0.3% [ 43 , 44 ] for HCV/HIV-coinfected patients after liver transplantation.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, about one out of three non-listing reasons was inappropriate or premature referral. This is in line with other experiences[ 22 - 27 ] including those reported in a study in Tampa (United States) that was conducted among 242 evaluated candidates who were not listed for liver transplantation during the 2004–2006 period; retrospectively, the most common reasons behind non-listing were early referrals, psychosocial factors, and medical contraindications[ 30 ]. On the one hand, early referral undoubtedly entails a cost (for patients, family members, and healthcare providers) and subtracts the availability of resources from other candidates.…”
Section: Discussionsupporting
confidence: 85%
“…A cohort study on 337 adult patients evaluated in London Ontario, Canada, in the 2009–2011 timeframe documented a non-listing rate of 49.3%[ 26 ]. According to the report by Mount Sinai Medical Center in New York, its non-listing rate was 58% in the 2000–2012 timeframe, reaching a rate of 82% in the HIV-positive population[ 27 ]. These older studies refer to an era in which the effect of anti-HBV and anti-HCV antiviral treatments had not yet been routinely applied; in recent years, waitlist registrations for HBV and HCV patients have been drastically reduced because of decompensation, persisting only registrations because of HCC, HDV co-infection or HBV-related ALF[ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have reported similar data . On the other hand, patients coinfected with HCV and HIV have lower access to LT compared to patients with HCV monoinfection . Moreover, Subramanian et al reported a higher mortality rate (14.4% versus 10.5%; P > 0.05) for coinfected patients on the waiting list compared to monoinfected patients.…”
Section: Discussionmentioning
confidence: 79%
“…(17,18) On the other hand, patients coinfected with HCV and HIV have lower access to LT compared to patients with HCV monoinfection. (14,19) Moreover, Subramanian et al (20) reported a higher mortality rate (14.4% versus 10.5%; P > 0.05) for coinfected patients on the waiting list compared to monoinfected patients. In addition, a significantly lower proportion of HIV-positive transplant candidates than HIV-negative patients underwent LT during the study period.…”
Section: Discussionmentioning
confidence: 99%